Impact of Bone Marrow Mesenchymal Stem Cells on Different Body Organs of Albino Rats Exposed To Cadmium Chloride Toxicity: A Systematic Review - Elham H. Ahmed 1, Mohammed E. Grawish2 , Mohamed Abdulrahman3 , Menatalla M. Elhindawy4 , Mohamad E. (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background and Objective: Cadmium chloride (Cd cl2) is a highly toxic heavy metal that causes severedegenerative effects to different body organs. Bone marrow mesenchymal stem cells (BMMSCs) may havea protective effect upon CdCl2 induced structural and functional changes in the rat’s organs. This systematicreview aimed to test the regenerative effects of bone marrow?derived mesenchymal stem cells on differentbody organs of albino rats exposed to cadmium chloride toxicity.Methods: Experimental animal studies were identified by the following electronic databases: PubMed,Scopus, Ovid Medline, KoreaMed, Google Scholar, Latin American and Caribbean Health SciencesLiterature (LILACS) and Central Cochrane Library. The literature search was done from January 2010 to2020.Conclusion: From the selected articles, using stem cell therapy enhances the regeneration process in CdCl2toxicity of different body organs.